Anthocyanin color stabilization by host‐guest complexation with p‐sulfonatocalix[n]arenes - Mendoza, Johan (2021)
Funding Information: Funding: This research was supported by the Associated Laboratory for Sustainable Chemistry, Clean Processes and Technologies LAQV through national funds from UIDB/50006/2020. FCT/MCTES is also acknowledged for supporting the National Portuguese NMR Network (ROTEIRO/0031/2013‐PINFRA/22161/2016, co‐financed by FEDER through COMPETE 2020, POCI, PORL, and FCT through PIDDAC) and for the grant PTDC/QUI‐COL/32351/2017. J.M. is grateful for the doctoral grant awarded by CONACYT (MEX/Ref. 288188). N.B. acknowledges FCT for the contract CEECIND/00466/2017.